The Legal Nature Of Contract And Contractual Obligations In Civil Law - Umirzokov, Shohrukh; Abdurakhmonov, Sultonbek (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the legal nature, substance, and distinctive characteristics of contracts and contractual obligations, which constitute a key institution of civil law. The discussion also addresses the role of a contract as a basis for creating obligations, as well as the rights and duties of the parties involved.